The Decolonizing the Papuan Body: Hybridity and Identity Politics in Jecko Siompo’s Animal Pop Choreographic Practice: Dekolonisasi Tubuh Papua: Hibriditas dan Politik Identitas dalam Praktik Koreografi Pop Hewan Jecko Siompo - Frans Junias Jugganza; Muhammad Ilham Mustain Murda; Hilmar Farid; Yola Yulfianti (Universitas Negeri Surabaya, 2026)
In Indonesia's contemporary dance landscape, the Papuan body is often caught in the tug-of-war between the legacy of colonial representation and the dynamics of urban modernity. This article aims to analyze how Jecko Siompo's Animal Pop rearticulates Papuan identity through choreographic practices in Jakarta. The research uses a qualitative approach with a case study design, through visual observation of the work, archival review, and continuous engagement with the choreographer's artistic environment. The findings show that Animal Pop does not simply combine Papuan movements and global hip-hop, but rather presents a body practice that simultaneously negotiates ecological memory, references to fauna movements, and urban rhythms. The dancer's body serves as a living archive that maintains the tendency of environment-based movement while responding to the demands of metropolitan life. Movement patterns such as grounded postures, asymmetrical articulation, and rhythmic transitions indicate the existence of repeated embodied negotiation processes . This article concludes that Jakarta is not only a production space, but also an important site in the transmission and reformulation of Papuan identity, especially through Jecko Siompo's artistic and pedagogical practice. Through the perspective of decolonial aesthetics, Animal Pop shows that decolonization does not take place as an abstract discourse, but as a living, situational, and continuously negotiated practice of movement. These findings contribute to the development of the study of contemporary dance, particularly in understanding the body as a medium of articulation of cultural identity and memory in urban spaces.